Violence against women in Peruvian infotainment shows - Delgado, Claudia (2014)
The article presents journalistic infotainment which is the combination of information and entertainment that gives priority to emotions. In Peru, the recurrent topic on television is violence against women. This type of news is widely presented on the media as the case of a cumbia dancer who was attacked by her partner – a singer. Since the leading roles were two members of the Peruvian showbiz, the matter was widely presented by newscasts and entertainment news programs. However, few weeks later the news was given diminished attention and another story came to fore. In the latter, a young woman was killed by her boyfriend after she participated in a TV show where she had earned money for exposing herpersonal problems. Finally, it is explained that in infotainment people become “popular” on the media, where bloody details are more important than finding a solution to the realproblem. In these situations the broadcast formula is repeated: the image is above other considerations.